The economic benefits of health and prevention in a high-income country: the example of Germany - Marc Suhrcke; Dieter M. Urban; Kim Moesgaard Iburg; David Schwappach; Till Boluarte; Martin McKee (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
This paper complements the current health policy debate, which is largely confined to the cost aspects of health systems, by considering explicitly the potential economic benefits of investing in health in general and via - chiefly primary - prevention. While concerns about high and rising health care costs are justified, we see a pressing need to also measure the benefits, ultimately enabling a complete economic assessment of the socially optimal level of resources for health. Despite the use of Germany as our point of reference, our approach and findings likely apply to a wider set of European highincome countries. Using new and already existing data, we find that in sheer health terms Germany has a lot to gain from more and better illness prevention. Assuming part of this existing burden can be reduced via effective preventive interventions, we find that the resulting economic benefits - expressed in people's willingness to pay for a reduction in mortality risk - would be substantial. We also gather Germany-specific evidence to suggest that the existing burden of ill health - whether caused by lack of prevention or treatment - negatively impacts a number of important economic outcomes at the individual and macro-economic level. Referring to work carried out in parallel to this project, we find that a number of cost-effective, primary preventive interventions exist to tackle part of the avoidable disease burden. Yet we note a deficit of economic evaluations, in particular in non-clinical interventions - a finding that underlines the role of government in the production of research on specifically non-clinical prevention. In light of the market failures discussed, from an economic perspective the role of government not only consists of research, but also - surprisingly to many - extends to actual interventions to address the health behaviour-related determinants of chronic disease. With the stakes as high and the economic justification for action in place, the case for scaling up preventive efforts in Germany, backed up by solid epidemiological and economic research, is hard to deny. – – Die vorliegende Studie ergänzt die gegenwärtige gesundheitspolitische Debatte, die sich vorwiegend auf Kostenaspekte des Gesundheitswesens konzentriert, indem sie den potentiellen ökonomischen Nutzen von Gesundheitsinvestitionen im allgemeinen und (Primär-)Prävention im besonderen hervorhebt. Auch wenn die Sorge um hohe und steigende Kosten des Gesundheitswesens berechtigt ist, bleibt die Notwendigkeit, auch den Nutzen der Gesundheitsausgaben zu erfassen, um somit zu einer ökonomisch vollständigen Einschätzung des sozial optimalen Niveaus der Gesundheitsausgaben zu gelangen. Trotz des Fokus auf Deutschland sind unser Ansatz und die Ergebnisse auch auf andere Mitgliedsländer der EU übertragbar. Wir zeigen anhand neuer und schon bekannter Daten, dass der Spielraum für Gesundheitsverbesserungen, vorwiegend durch Prävention, in Deutschland erheblich ist. Der ökonomische Nutzen - gemessen an der Zahlungsbereitschaft der Bevölkerung - der durch Reduktion eines Teils dieser Krankheitslast mittels Interventionen erzielt werden kann, ist nach unseren Berechnungen beachtlich. Darüber hinaus zeigen mehrere Studien, wie die aktuell gegebene Krankheitslast, ob durch einen Mangel an Prävention oder Versorgung verursacht, eine Reihe relevanter ökonomischer Grössen auf individueller und gesamtwirtschaftlicher Ebene beeinträchtigt. Wie eine parallel durchgeführte Studie der Autoren ergab, existieren auch eine Reihe kosten-effektiver Interventionen im Bereich der primären Prävention. Dennoch bestehen noch Lücken in der ökonomischen Bewertung insbesondere nicht-klinischer Interventionen - ein Ergebnis, das die Rolle des Staates in der Evaluation dieser Interventionen unterstreicht. Aufgrund von Marktversagen in einigen relevanten Bereichen besteht eine ökonomische Rechtfertigung für staatliches Handeln nicht nur im Bereich der Forschung, sondern - überraschend für manche - auch im Bereich der (Primär-)Prävention der nicht-ansteckenden und mit dem individuellen Gesundheitsverhalten verbundenen Krankheiten. Aufgrund des in diesem Papier dokumentierten hohen gesundheitlichen und ökonomischen Nutzens sowie der ökonomischen Rechtfertigung der Rolle des Staates kann das Argument für eine Verstärkung der Prävention in Deutschland nur schwer bestritten werden.
Keywords: 300; Gesundheitswesen; Gesundheitskosten; Kosten-Nutzen-Analyse; Gesundheitsvorsorge; Deutschland